Knowledge and Practice regarding Self-Care among the patients with type II Diabetes of Kapan, Kathmandu - Sharma, Saraswati; Bhadari, Sushila Devi (Journal of Advanced Academic Research, 2017)
Introduction: Diabetes is considered as one of the chronic health problems and the 6th leading cause of mortality in the world. Self-management of diabetes involves a number of considerations and choices that the patient with Diabetes must make on a daily basis. It requires that patients are able to reconcile their resources, values and preferences with a therapeutic of a healthy diet, exercise, no smoking, low or no alcohol intake, glucose monitoring and for some patients, medication. Objective: To assess the knowledge regarding Self-Care and practice among the patients with type II Diabetes in Kapan muncipality Kathmandu. Methods: Descriptive cross sectional study was adopted to assess the knowledge regarding Self-Care and the practice among the patients with type II Diabetes. The study population was 100and study period was From 2014 September 15-October15 in Kapan, Kathmandu. Result: The study was carried out in 100 respondents among them the majority 30 % respondent have adequate knowledge and 12% respondent have inadequate knowledge. In these respondents practice seem to be sufficient. Among the 58 respondent, majority of the respondents (38%) have insufficient knowledge and (20%) have sufficient. Knowledge and in these respondents practice seems to be inadequate. The result shows that majority (58%) of the respondents has inadequate practice and (42%) had adequate practice. There was equal percentage of sufficient and insufficient knowledge among respondents i.e. 50%. Conclusion: The present study concluded that respondents who have sufficient knowledge have adequate practice about self-care majority of the respondents having insufficient knowledge have inadequate practice.